2015
DOI: 10.1371/journal.pone.0120803
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Differentiation Potential of Human Adipose-Derived Stem Cells Grown on Chitosan Hydrogel

Abstract: Applied tissue engineering in regenerative medicine warrants our enhanced understanding of the biomaterials and its function. The aim of this study was to evaluate the proliferation and differentiation potential of human adipose-derived stem cells (hADSCs) grown on chitosan hydrogel. The stability of this hydrogel is pH-dependent and its swelling property is pivotal in providing a favorable matrix for cell growth. The study utilized an economical method of cross linking the chitosan with 0.5% glutaraldehyde. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 41 publications
3
29
0
5
Order By: Relevance
“…Especially, chitosan hydrogel increased the proliferation rate of MSCs; the doubling time of MSCs was ≈70 h in chitosan hydrogel and ≈80 h in tissue culture plate. [14a] This result showed that relative doubling time reduction is similar between MSC in hydrogel (1.1 times) and NV‐treated MSCs (1.18 times); i.e., that the proliferation rate of MSCs is influenced by their environment, and that the proliferation effects of NVs on MSCs could facilitate their application to stem‐cell engineering.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Especially, chitosan hydrogel increased the proliferation rate of MSCs; the doubling time of MSCs was ≈70 h in chitosan hydrogel and ≈80 h in tissue culture plate. [14a] This result showed that relative doubling time reduction is similar between MSC in hydrogel (1.1 times) and NV‐treated MSCs (1.18 times); i.e., that the proliferation rate of MSCs is influenced by their environment, and that the proliferation effects of NVs on MSCs could facilitate their application to stem‐cell engineering.…”
Section: Resultsmentioning
confidence: 92%
“…To improve the clinical potential of MSCs, researchers have developed a hydrogel‐based culture system that mimics the natural extracellular matrix. Collagen, chitosan, and HA hydrogels were used to maintain the stemness of MSCs and to improve engraftment in vivo . Especially, chitosan hydrogel increased the proliferation rate of MSCs; the doubling time of MSCs was ≈70 h in chitosan hydrogel and ≈80 h in tissue culture plate.…”
Section: Resultsmentioning
confidence: 99%
“…But currently the research is directed towards the use of biomaterials as scaffolds for cell differentiation and regeneration.3D culture systems have frequently been used to mimic in vivo conditions [12,13]. Our previous reports have confirmed that hADSCs can be easily harvested, cultured and differentiated into chondrogenic lineage [14]. Based on their morphological features and phenotypic analysis by flow-cytometry, cells from the third passage were used in the 3-D culture systems.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance was measured at 570 nm. Cell viability is expressed as percentage of that in the control group (Debnath et al 2015).…”
Section: Mtt Assaymentioning
confidence: 99%